Novel 3-Methyl-1,6-Diazaphenothiazine as an Anticancer Agent—Synthesis, Structure, and In Vitro Anticancer Evaluation - Beata Morak-Młodawska; Emilia Martula; Małgorzata Jeleń; Artur Beberok; Zuzanna Rzepka; Sebastian Musiał; Szymon Małek; Marta Karkoszka-Stanowska; Dorota Wrześniok (Molecules, 2025)
Pyridine derivatives are widely distributed in nature and have valuable pharmacological properties. The pyridine core can be found in drugs such as sorafenib, zapiclone or prothipendyl. Dipyridothiazines are derivatives of phenothiazines that exhibit valuable anticancer, antioxidant and immunomodulatory activities. In this study, we present the synthesis and preliminary in vitro analysis of anticancer activity towards melanotic (COLO829, G361) and amelanotic (A375, C32) melanoma cells and normal human fibroblasts (HDF) of a series of new tricyclic diazaphenothiazines containing a pyridine scaffold in their structure. The structures of these new molecules was confirmed using spectral techniques, including 1H NMR, 13C NMR, 2D NMR and HRMS. An in vitro panel of experiments was assessed using the WST-1 assay and cytometric techniques. The two most promising compounds were analyzed for their effect on intracellular GSH levels, mitochondrial membrane potential and their ability to initiate DNA fragmentation to determine the potential mechanism of both cytotoxic and proapoptotic activity. The conducted studies confirmed the ability of the new 3-methyl-1,6-diazaphenothiazines to induce apoptosis in cancer cells, especially in terms of inducing initial as well as late-phase apoptosis. Moreover, the studied compounds were found to induce redox imbalance (evidenced by GSH depletion) in the analyzed melanoma cells, which may be an important factor that directs melanoma cells towards cell death signaling pathways.